Illness Uncertainty Longitudinally Predicts Distress Among Caregivers of Children Born With DSD. (26th September 2020) - Roberts, Caroline M; Sharkey, Christina M; Bakula, Dana M; Perez, Megan N; Delozier, Alexandria J; Austin, Paul F; Baskin, Laurence S; Chan, Yee-Ming; Cheng, Earl Y; Diamond, David A; Fried, Allyson J; Kropp, Bradley; et al.
Abstract: Objective: A subset of parents of children with disorders/differences of sex development (DSD) including ambiguous genitalia experience clinically elevated levels of anxious and depressive symptoms. Research indicates that uncertainty about their child's DSD is associated with parent psychosocial distress; however, previous studies have been cross-sectional or correlational in nature. The current study is the first to examine the longitudinal trajectory of the relationship between caregiver-perceived uncertainty about their child's DSD and caregiver anxious and depressive symptoms across the first 12 months following genital surgery in young children, or if surgery was not performed, the first 12 months following study entry. Methods: One hundred and thirteen caregivers ( M age = 32.12; 57.5% mothers; 72.6% Caucasian) of children ( N =  70; M age = 9.81 months; 65.7% female) with DSD were recruited from 12 DSD specialty clinics in the United States. Caregivers completed psychosocial measures at baseline, 6 and 12 months following genitoplasty, or study entry if parents elected not to have surgery for their child. Results: Caregiver illness uncertainty and both anxious and depressive symptoms were highest at baseline and decreased over time ( ps < .05). Caregiver illness uncertainty predicted symptoms of anxious and depressive symptoms across all time points ( p s < .05). Conclusions: Caregivers' perceptions of uncertainty about their child's DSD are highest soon after diagnosis, and uncertainty continues to predict both anxious and depressive symptoms across time. Thus, the initial diagnostic period is a critical time for psychological assessment and intervention, with parent illness uncertainty being an important clinical target.